Historicising the Popular: Trans-Atlantic Exchanges between African American and Local South African Musicians during the Cultural Boycott, c. 1960-1993 - Waggie, Ashrudeen (Stellenbosch : Stellenbosch University, 2026)
Thesis (PhD)--Stellenbosch University, 2026.